Le parc des Docks à Saint-Ouen (Seine-Saint-Denis). Entre passé industriel et écologisation du site : quel héritage humain et pédologique ? - Élisabeth Rémy; Marine Canavese; Nathalie Berthier; Yves Petit-Berghem (In Situ)
The docklands park at Saint-Ouen, a suburb to the north of Paris in the Seine-Saint-Denis department, is intimately associated with the place’s industrial history. In recent decades, the industrial activities were essentially comprised of battery production and an oil storage depot. Today, one of the major issues is the urban renewal of these former industrial spaces. The creation in 2013 of a new ‘eco-district’ linking the centre of Saint-Ouen to the river Seine aimed at giving this territory a new future without turning its back on its historic heritage. The project involved the creation of a twelve-hectare park along the banks of the Seine. Industrial brownfield sites have been rehabilitated into zones of circulation for cyclists and pedestrians, with spaces for meetings, for culture and for educational practices and sharing, associated with gardening. The gardening activities within the park, baptised the island of sharing (‘île des partages’), are based on the presence of former workers’ allotment gardens dating back to the suburb’s industrial heyday, associated with more recent forms of community gardens run by various associations, by public bodies and, above all, by individual gardeners, each cultivating a few square metre of the collective gardens. The difficulty is the cohabitation of these different types of gardening activity in a place already charged with history and where the question of the pollution of the soil is more or less properly understood by the different stakeholders. Another question concerns the involvement of the individual gardeners confronted with new projects supported by the local authorities which are anxious to keep these gardens as a common property, open to all. Confronted itself with strategies of withdrawal and reluctance to share, the local authorities are trying to encourage the civic appropriation of nature in the city, to encourage the collective management of public spaces and to reinforce the skills and know-how associated with the history of the place. What can be done to ensure the recognition of the heritage value of these different gardens? What kind of heritage should be recognised? Can these community gardens become a shared asset that can be passed on to future generations? These are some of the questions that the article looks at.